Tingkat Keterlibatan Lembaga Keuangan Syariah Dalam Pemberdayaan UMKM di Indonesia - Gunawan Aji; Miladia Nur Kamila; Nisa Usifa; Indah Setiowati (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the important sectors in the Indonesian economy. MSMEs contribute 60.7% to Indonesia's GDP, absorb 97% of the workforce, and support 99% of Indonesia's population. Therefore, empowering MSMEs is one of the government's priorities in order to increase economic growth and community welfare. The research in this article uses qualitative research methods. In this research, to obtain information or data on these problems comes from literature (library research). This research uses processing and analysis of secondary data collected through literature study and secondary data analysis. Islamic financial institutions have the potential or significant influence on the growth of micro, small and medium enterprises. Considering that capital is the weak point of MSMEs. With the existence of sharia financial institutions, business actors have access to greater capital and can achieve their goals in business development.